Pridobivanje dovoljenj za zamenjavo uparjalnikov in povečanje moči JE Krško - Špiler, Jože (Strojniški vestnik, 2000)
The aim of this paper is to online the most important parts of the nuclear safety licensing process, which has been pursued continuously during the last three years. The present Slovenian regulatory system is essentialy based on the laws and regulations which were passed in the 1980s by the former Yugoslavia and have remained in force in the Republic of Slovenia following its independence in 1991. The paper reviews the laws and regulations applicable to the licensing of Krško nuclear power plant (NPP). The integrated licensing process of the steam generators replacement and the uprating at Krško NPP can be divided into two groups: - nuclear-safety-related licensing process, - non nuclear licensing process.
Keywords: pridobivanje dovoljenj; specifikacije tehnične; poročila varnostna; okna obratovalna; Nuklearna elektrarna Krško; zamenjava uparjalnikov; jedrska varnost; dovoljenja